(untitled) (REMUNOM, 2024)
The participation of dental surgeons in the hospital environment within multidisciplinary teams is fundamental, since hospital dentistry carries out practices that correlate oral health and the individual’s systemic health. Unfortunately, this context is not common. There needs to be an awareness that hospital dentistry effectively contributes to the rehabilitation of patients, as hospital environments are especially susceptible to the risk of contracting infectious and pulmonary diseases. Patients in Intensive Care Units (ICUs) need extra care because their immunity is compromised, increasing the occurrence of oral infections due to the oral cavity being a reservoir of microorganisms, many of them harmful. The purpose of this study was to carry out a literature review in order to emphasize the importance of the role of the dental surgeon in a multidisciplinary health team, i.e. in groups of professionals from different specialties who work in a collaborative and integrated manner, with the aim of providing more complete and personalized care to the patient. The Scielo, PubMed, Medline, Google Scholar, LILACS databases and other publications were consulted using the following key words in Portuguese and English: dentistry, hospital dentistry unit, intensive care units, from 2005 to 2024.